Contesting crime science : our misplaced faith in crime prevention technology - Kramer, Ronald (Senior lecturer); Oleson, James C., 1968- (University of California Press, 2022)
"In this eye-opening critique, Ronald Kramer and James C. Oleson interrogate the promises of crime science and target our misplaced faith in technology as the solution to criminality. This book deconstructs crime science's most prominent manifestations--biological, actuarial, security, and environmental sciences. Rather than holding the technological keys to crime's resolution, crime sciences inscribe criminality on particular bodies and constitute a primary resource for the conceptualizations of crime that many societies take for granted. Crime science may strive to reduce crime, but in doing so, it reproduces power asymmetries, creates profit motives, undermines important legal concepts, instantiates questionable practices, and forces open new vistas of deviant activity"--